Competition policy with optimally differentiated rules instead of per se rules vs. rule of reason - Arndt Christiansen; Wolfgang Kerber (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2006)
Both in US antitrust and EU competition policy a development to a broader appli-cation of rule of reason instead of per se rules can be observed. In the European discussion the attempt to base competition policy on a more economic approach is mainly viewed as im-proving the economic analysis in the assessment of specific cases. In this paper it is shown from a general law and economics perspective that the application of rules instead of focus-sing on case-by-case analyses can have many advantages (less regulation costs, rent seeking and knowledge problems), although an additional differentiation of rules through a deeper assessment can also have advantages in regard to the reduction of decision errors of type I and II. After introducing the notion of a continuum of more or less differentiated rules, we show - based upon law and economics literature upon the optimal complexity of rules - in a simple model that a competition rule is optimally differentiated, if the marginal reduction of the sum of error costs (as the marginal benefit of differentiation) equals the marginal costs of differen-tiation. This model also allows for a more detailed analysis of the most important determi-nants of the optimal degree of rule-differentia¬tion. From this law and economics perspective, competition policy should consist mainly of (more or less differentiated) rules and should only rarely rely on case-by-case analysis. Therefore the main task of a more economic ap-proach is to use economics for the formulation of appropriate competition rules.
Keywords: K21; K40; L40; 330; Competition Policy; European Competition Law; Rule of Reason; Wettbewerbspolitik; EU-Politik; EU-Staaten; USA